Socialization, Awareness, Tax Sanctions and WPOP MSME Compliance - Ni Putu Ika Wahyudiana Putri; Putu Ery Setiawan (E-Jurnal Akuntansi, 2024)
This research aims to analyze individual taxpayers with micro, small and medium business ownership (MSME). This research focuses on empirically testing the effect of socialization, awareness, and tax sanctions on MSME WPOP compliance. All 5,809 MSME WPOPs in West Denpasar KPP Pratama will be the population in this research with a sample of 98 people. Purposive sampling technique was used in this researche with multiple linear regression analysis as a tool in conducting research testing. The findings show that tax socialization, taxpayer awareness, and tax sanctions have a positive effect on MSME WPOP compliance. It is hoped that this research will become a reference and consideration in policy making as an effort to increase taxpayer compliance